Odpowiedzi

Najlepsza Odpowiedź!
2009-12-11T11:16:00+01:00
A)
2x-3=3(1-x)
2x-3=3-3x
2x+3x=3+3
5x=6
x=5/6

b)
2x-(3-x)=⁴₃(6x-3)
2x-3+x=8x-4
3x-8x=-4+3
-5x=-1
x=1/5

c)½(3x-2)=(¼-½x)
3/2x-1+1/2x=1/4
2x=1/4+1
2x=5/4
x=5/8

d)2x+4=-4(x+3)
2x+4=-4x-12
2x+4x=-12-4
6x=-16
x=16/6
x=2 2/3


Odp. jest rozwiazaniem równania b)
2009-12-11T11:21:44+01:00
A)2x-3=3(1-x)
2x-3=3-3x
2x+3x=3+3
5x=6/:5
x=1⅕

b)2x-(3-x)=⁴₃(6x-3)
2x-3+x=8x-4
3x-8x=-4+3
-5x=-1
x=¹/₅

c)½(3x-2)=(¼-½x)
1½x-1=¼-½x
1½x+½x=¼+1
2x=1¼/:2
x=1¼*½
x=⁵/₈

d)2x+4=-4(x+3)
2x+4=-4x-12
2x+4x=-12-4
6x=-16/:6
x=-2⅔

odp: b